Ring opening polymerization of dilactide using salen complex as catalyst - Idage, Bhaskar B.; Idage, Susheela B.; Kasegaonkar, A. S.; Jadhav, R. V. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
The recent concerns about our environment have led to search for environmentally benign and sustainable materials that could substitute the more commonly used petroleum based materials. Biodegradable and sustainable polylactide (PLA) is becoming one of the most promising and practical materials as a partial replacement for the petroleum-based materials. The commercially available PLA is generally homochiral poly(L-lactide) (PLLA) at present because L-lactic acid with high optical purity can only be obtained in bulk by fermentation of carbohydrate. PLLA is mostly synthesized by ring opening polymerization (ROP) of homochiral L-lactide (LLA), which is a cyclic dimer of L-lactic acid. In the present work, poly(L-lactide)s were synthesized by the ring opening polymerization (ROP) of L-lactide using iron and manganese salen complexes as catalyst. The new iron and manganese salen complexes were synthesized, purified, characterized and used as catalyst for polymerization of L-lactide. The poly(L-lactide)s prepared were characterized by infrared, proton NMR spectroscopy, solution viscosity, gel permeation chromatography, thermal analysis and X-ray diffraction. (C) 2009 Elsevier B.V. All rights reserved.
Conference on Specialty Advanced Materials and Polymers for Aerospace and Defense and Applications (SAMPADA-2008), Mat Res Soc Singapore, Singapore, SINGAPORE, JUL 03-08, 2005
Keywords: Gel permeation chromatography; Iron salen catalyst; L-Lactic acid; L-Lactide; Manganese salen catalyst; Poly(L-lactide); ring opening polymerization; Solution viscosity

Ring opening polymerization of lactide: kinetics and modeling - Metkar, Sangeeta; Sathe, Vivek; Rahman, Imran; Idage, Bhaskar; Idage, Susheela (Chemical Engineering Communications, 2019)
The ring opening polymerization (ROP) kinetics of L-lactide was studied in bulk at 150, 160, and 180 degrees C using stannous octoate [Sn(Oct)(2)] catalyst and 1-pyrene butanol co-catalyst. The effect of different parameters namely, time and co-catalyst to catalyst ratio was studied on the properties of polylactide. The experimental results showed high conversion of L-lactide. The kinetics of L-lactide ROP follows the co-ordination insertion mechanism. The experimental results obtained were studied to account for the reversible activation, propagation, termination, and validated by modeling using MATLAB. The model developed successfully predicts the monomer conversion and the kinetics of L-lactide ROP.
Keywords: 1-pyrene butanol; Average molecular weights; GPC; kinetics; L-Lactide; Modeling and simulation; Polymerization temperature; Proton NMR; ROP; Stannous octoate

Biodegradable, solvent-free photocrosslinkable PLLA resin formulations for additive manufacturing - Pal, Shibam; Asha, S. K. (Macromolecular Chemistry and Physics, 2022)
Acrylate end-functionalized linear and star poly l-lactide (PLLA) based aliphatic, photocurable oligomeric crosslinkers are developed, which are formulated with hydroxyl (ethyl)methacrylate (HEMA) as a biodegradable reactive diluent to demonstrate successful application for solvent-less 3D printing using digital light processing (DLP) technique as well as a custom-designed direct ink writing 3D printer. The resin formulation for 3D printing is optimized using spot curing, photodifferential scanning calorimetry and cure depth analysis. The 3D printed parts exhibit promising mechanical property along with improved hydrophilicity and biodegradability. The development of new photocurable resin formulations are expected to meet the growing demand for raw materials that can be applied for developing custom designed bio implantable objects.
Keywords: 3D printing; biodegradable materials; digital light processing; L-Lactide; photocurable materials